2022
DOI: 10.1088/1361-6668/ac5164
|View full text |Cite
|
Sign up to set email alerts
|

Improving the connectivity of MgB2 bulk superconductors by a novel liquid phase sintering process

Abstract: This work investigates a new processing method developed to improve the connectivity of ex-situ MgB2 bulks at low sintering temperatures. Mg additions (1 − 10 wt.%) were mixed to pre-synthesised MgB2 to make composite powders that were sintered at 900 ffiC by the Field Assisted Sintering Technique (FAST). Addition of 10 wt.% Mg resulted in a substantial increase in density from 68 to 79% and a dramatic reduction in MgB4from 11 to ∼ 0 wt.%. Pressure and dilatometry data recorded in-situ during the sintering proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The latter are more likely to serve as effective flux pinning centres owing to their size. Moreover, the formation of small Mg-N-B impurities also results in Mg as a by-product, which may improve grain connectivity and enhance low-field performance, similar to the effect of adding excess Mg to MgB2 powders before sintering [34]. Even though Mg-N-B impurities are situated at grain boundaries, the density is low enough not to impede macroscopic current transport.…”
Section: Superconducting Properties and Correlation With Microstructurementioning
confidence: 99%
“…The latter are more likely to serve as effective flux pinning centres owing to their size. Moreover, the formation of small Mg-N-B impurities also results in Mg as a by-product, which may improve grain connectivity and enhance low-field performance, similar to the effect of adding excess Mg to MgB2 powders before sintering [34]. Even though Mg-N-B impurities are situated at grain boundaries, the density is low enough not to impede macroscopic current transport.…”
Section: Superconducting Properties and Correlation With Microstructurementioning
confidence: 99%
“…Powders (∼3 g) after milling for 6 h were pressed into disc-shaped pellets for consolidation. Based on our preliminary work [25], 5 wt.% Mg addition was used in this study. Mg powder (purity: 99.8%, Alfa Aesar) was homogenously mixed by hand with ball-milled MgB 2 powder.…”
Section: Methodsmentioning
confidence: 99%
“…They found that liquid phases can form during the sintering which helps improve the bulk density. Therefore, the low-field J c was enhanced by Mg additions, in particular 6 wt.% and 10 wt.% Mg [25]. However, large pores up to hundreds of microns still remain in their best sample.…”
Section: Superconducting Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several processes have been developed for MgB2 bulk fabrication, including the in-situ method [4], [6]- [9], in which a mixed powder of magnesium and boron reacts; the high-pressure synthesis method [10]- [16]; the diffusion method using liquid magnesium [17], [18]; and liquid phase assisted sintering [19]. In the conventional in-situ method, the packing factor of MgB2 is as low as around 50%, since the density of reacted MgB2 is higher than the density of the Mg/B precursor powders [6], [7].…”
Section: Introductionmentioning
confidence: 99%